Atorvastatin Prevents the Neuron Loss in the Hippocampal Dentate Gyrus Region through its Anti-Oxidant and Anti-Apoptotic Activities - Yadollah-Damavandi, Soheila; Sharifi, Zahra N.; Arani, Hamid Z.; Jangholi, Ehsan; Karimi, Aliasghar; Parsa, Yekta; Movassaghi, Shabnam (CNS & Neurological Disorders - Drug Targets, 2021)
Background: Atorvastatin is a member of statins, which has shown positive vascular effects, anti-oxidant, anti-platelet, and anti-apoptotic properties. Objective: In this study, we hypothesized that atorvastatin could prevent the neurons lost in the hippocampal dentate gyrus region after transient global Ischemia/Reperfusion (I/R) through its anti- oxidant and anti-apoptotic activities. Method: Twenty-four male Wistar rats, 12-13 weeks old and weighing 250–300 g, were divided randomly into four groups: control, I/R, vehicle (I/R treated with NaCl) and experiment (I/R treated with atorvastatin, 10 mg/kg); rats were sacrificed 96 hours after I/R. Quantitative expression of genes (caspase 8, p53, bax, bcl2, cytochrome c) was studied. The MDA level, SOD, CAT, and GPx activities were measured with biochemical tests. To detect apoptotic cells, TUNEL and Nissl staining were performed. Mitochondria were prepared from the hippocampus rats and used for the quantification of mitochondrial ROS, ATP level, GSH content, membrane potential, cytochrome c release, and determination of mitochondrial swelling. Results: Atorvastatin attenuated the overexpression of bax, cytochrome C, p53, and caspase8 mRNAs and induced expression of bcl-2 mRNA (P<0.001). Atorvastatin treatment increased anti-oxidant enzyme levels (P<0.01). Treatment with atorvastatin reduced the number of TUNEL-positive cells. It could decrease the cytochrome c release (P<0.01), inhibit the decrease of MMP (P<0.001) and increase the ATP level (P<0.001) in hippocampal mitochondria compared with the I/R group. Conclusion: Atorvastatin treatment in I/R rats decreases oxidative stress, production of ROS, apoptosis rate in neuronal cells, and improves the mitochondrial function. Hence, atorvastatin has a proper neuronal protective effect against the I/R injury in the brain.
Keywords: oxidative stress